2020
DOI: 10.3389/fneur.2020.538301
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics: Recent Advances and Its Role in the Treatment of Alzheimer's Disease

Abstract: Objective: This review summarizes recent findings on the epigenetics of Alzheimer's disease (AD) and provides therapeutic strategies for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 205 publications
0
23
0
Order By: Relevance
“…The histone marker H4K16ac causes an alteration in the chromosome which connects it with DNA damage and aging in neurodegenerative diseases. The amount of H4K16a in the aged brain decreases due to the aged brain’s inability to regulate it, which results in changes in brain function [ 100 , 101 ]. An in vitro study on AD found that methylation levels in the 2′,5′-oligoadenylate (2-5A) synthetase gene were reduced [ 102 ].…”
Section: Role Of Dna Methylation In Neurological Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The histone marker H4K16ac causes an alteration in the chromosome which connects it with DNA damage and aging in neurodegenerative diseases. The amount of H4K16a in the aged brain decreases due to the aged brain’s inability to regulate it, which results in changes in brain function [ 100 , 101 ]. An in vitro study on AD found that methylation levels in the 2′,5′-oligoadenylate (2-5A) synthetase gene were reduced [ 102 ].…”
Section: Role Of Dna Methylation In Neurological Disordersmentioning
confidence: 99%
“…The ANK1 gene’s elevated methylation profile demonstrated its role in AD [ 108 ]. OTX gene methylation changes also lead to AD [ 101 ].…”
Section: Role Of Dna Methylation In Neurological Disordersmentioning
confidence: 99%
“…However, there is no consensus in the literature on whether the methylation of APP, the amyloid precursor protein, is significantly altered in AD patients' brain [203][204][205]. Nevertheless, other AD-associated genes have been found to be differentially methylated in AD patients, such as APOE [206], PLD3 [207,208], and EPHA1 [201].…”
Section: Epigenetics In Alzheimer's Disease-related Memory Lossmentioning
confidence: 99%
“…This characteristic makes the miRNAs an exciting new approach to AD therapeutics. Although this area is still in the early stages, studies have shown evidence of several miRNAs that target important molecules in this pathology [ 29 , 111 , 112 , 113 , 114 ]. Table 4 shows some studies of miRNAs in AD, that can have a potential application as AD therapeutic tools.…”
Section: Therapeutic Applications For Alzheimer’s Diseasementioning
confidence: 99%